The Urgency of Professional Ethics as a Form of Legal Compliance in Realizing the Supremacy of Law - Prasetyo, Yogi (Law Review, 2024)
This article aims to explain the problem of professional ethics as a form of legal disobedience and also to explain the urgency of ethics in legal compliance in order to realize the supremacy of law. The background of legal problems in Indonesia is very complex, one important thing that must be considered is the issue of ethics of law enforcement officers. Not a few legal cases that occur are related to ethical violations committed by law enforcement officers themselves. These ethical violations show evidence of legal disobedience from law enforcement officers which has an impact on the low level of legal supremacy in this country. The research method used in this writing is a literature study with a philosophical approach. Literature materials are the main data for the study. Descriptive analysis is used to explain the research comprehensively. The results of the study show many problems of ethical violations committed by law enforcement officers, which are a form of disobedience to the law, so that with these problems the supremacy of law is in decline. Therefore, it is important and must be considered the problem of ethics for law enforcement officers in order to create legal compliance in order to realize the supremacy of law in Indonesia.